Longitudinal Assessment of Prognostic Understanding in Patients with Advanced Lung Cancer and Its Association with Their Psychological Distress. (23rd September 2021) - Arai, Daisuke; Sato, Takashi; Nakachi, Ichiro; Fujisawa, Daisuke; Takeuchi, Mari; Sato, Yasunori; Kawada, Ichiro; Yasuda, Hiroyuki; Ikemura, Shinnosuke; Terai, Hideki; Nukaga, Shigenari; Inoue, Takashi; et al.
Abstract : Background: Accurate prognostic understanding in patients with advanced cancer is essential for shared decision making; however, patients may experience psychological burden through knowing the incurable nature of advanced cancer. It has been unclear how their prognostic understanding fluctuates and whether accurate prognostic understanding is associated with psychological distress from the time of diagnosis over time. Materials and Methods: We longitudinally investigated prognostic understanding in 225 patients with newly diagnosed advanced lung cancer at 16 hospitals in Japan until 24 months after diagnosis. We examined associated factors with being consistently accurate in prognostic understanding, especially focusing on its association with psychological well-being. Results: The proportion of patients with an inaccurate prognostic understanding remained approximately 20% over time with the presence of patients with inconsistent understanding. Patients with consistently accurate prognostic understanding showed a significantly lower Emotional Well-Being subscale score at both 3 and 6 months after diagnosis ( p = .010 and p = .014, respectively). In multivariate analyses, being consistently accurate in prognostic understanding was significantly associated with female gender and higher lung cancer–specific symptom burden at 3 months ( p = .008 and p = .005, respectively) and lower emotional well-being at 6 months ( p = .006). Conclusion: Although substantial proportions of patients with advanced lung cancer had inaccurate prognostic understanding from the time of diagnosis over time, patients with consistently accurate prognostic understanding experienced greater psychological burden. Our findings highlight the importance of continuous psychological care and support for patients who understand their severe prognosis accurately. Implications for Practice: This study demonstrated that approximately 20% of patients with advanced lung cancer had an inaccurate understanding about their prognosis, not only at the time of diagnosis but also at the later time points. Being consistently accurate in prognostic understanding was significantly associated with elevated levels of psychological distress. Although accurate prognostic understanding is essential for decision making for treatment and advance care planning, health care providers should be aware of psychological burdens in patients that accept their severe prognosis accurately. Appropriate care and support for such patients are warranted from diagnosis over time. Abstract : Accurate illness understanding is crucial for patients with advanced cancer. This article reports on the association between being consistently accurate in prognostic understanding and psychological distress over time.